2001
DOI: 10.1021/ac001440b
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Atmospheric Pressure Laser Ablation-Mass Spectrometry

Abstract: We describe an atmospheric pressure nanosampling interface for mass spectrometry based on near-field laser ablation. Pulsed laser radiation is delivered to the sample surface through a near-field optical probe, and the ablation plume is sampled through a capillary orifice and analyzed by standard MS methods. A spatial resolution of less than 200 nm and a sensitivity below 2 amol is demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
100
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(102 citation statements)
references
References 42 publications
0
100
1
1
Order By: Relevance
“…The tip had a diameter aperture of around 170 nm, creating ablation craters with about the same diameter (see below). Molecular crystals (the same bis-triazene that was used as model compound for the triazene polymers in other studies, shown in Scheme 7) were applied as substrates, because the main goal of this study was the development of nanoscale atmospheric-pressure laser ablation-mass spectrometry [390].…”
Section: Snom Structuringmentioning
confidence: 99%
See 1 more Smart Citation
“…The tip had a diameter aperture of around 170 nm, creating ablation craters with about the same diameter (see below). Molecular crystals (the same bis-triazene that was used as model compound for the triazene polymers in other studies, shown in Scheme 7) were applied as substrates, because the main goal of this study was the development of nanoscale atmospheric-pressure laser ablation-mass spectrometry [390].…”
Section: Snom Structuringmentioning
confidence: 99%
“…Here, mainly the structuring is presented, but it was possible to detect the main product of the photochemical decomposition of the triazene group, N 2 , by mass spectrometry [390]. An array of ablation craters in the bis-triazene is shown in Fig.…”
Section: Snom Structuringmentioning
confidence: 99%
“…The typical spatial resolution of LA-ICP-MS, achieved with most commercially available laser ablation systems, ranges from 5 to 300 m [1, [6][7][8], and in some cases this would be insufficient, for example, for the analysis of the fine structures of small regions of biological tissues and single cells [9][10][11] or in nanoelectronics [12]. The known nearfield effect can be applied in order to improve the spatial resolution of the laser ablation, and this is being intensively investigated at present in several groups [13][14][15][16][17]. The idea of near-field laser ablation consisted in the formation of radiation intensity singularities by means of very small conductive objects (e.g., tip of a thin Ag needle) immersed in the radiation field.…”
Section: Introductionmentioning
confidence: 99%
“…Optical resolution in the nanometer range is achievable with this method. Efforts to use SNOM for LDI mass spectrometry were reported recently, but without success so far in detecting larger molecular ions [33].…”
mentioning
confidence: 99%